2001
DOI: 10.1088/0022-3727/34/14/318
|View full text |Cite
|
Sign up to set email alerts
|

Ac and dc electroluminescence in insulating polymers and implication for electrical ageing

Abstract: Electroluminescence detected in many different polymers under uniform 50 Hz ac and dc fields exhibits a threshold-like character, i.e. the light emission increases supralinearly with the applied voltage above a critical value called the emission threshold. The significance of this threshold is not straightforward. It could be a true physical threshold corresponding to the onset of the luminescence excitation as opposed to a sensitivity-limited threshold without specific significance. This paper discusses this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 15 publications
2
25
0
2
Order By: Relevance
“…This is in good agreement with a previous work performed with 50 mthick PEI commercial films [7]. Two different mechanisms may induce EL under a DC high field: recombinations of charges facing each other in the sample or impact excitation/ionization of luminescent centres by hot charge carriers.…”
Section: Electroluminescencesupporting
confidence: 93%
See 2 more Smart Citations
“…This is in good agreement with a previous work performed with 50 mthick PEI commercial films [7]. Two different mechanisms may induce EL under a DC high field: recombinations of charges facing each other in the sample or impact excitation/ionization of luminescent centres by hot charge carriers.…”
Section: Electroluminescencesupporting
confidence: 93%
“…Transition voltages from ohmic to SCLC regime of filled varnishes have been logically found to be lower than for pure varnish (Table 1). The slopes of the high field conduction current curves for both standard (already found to be higher than 2 in PEI [7]) and filled varnishes are higher than two. This may be explained by a charge carriers electric field dependent mobility in the high field region.…”
Section: Conduction Currentmentioning
confidence: 67%
See 1 more Smart Citation
“…Analysis of conduction processes and investigation of the field dependence of space charge profiles provide a way to tackle the problem. Combined EL and current measurements performed on different polymeric materials have shown a good correlation between the onset for permanent EL excitation and a change in the conduction mechanism as denoted by a steep increase of the slope of the current-field characteristic in a log-log representation [27]. Similarly, investigation of the spatial distribution of the space charge at different fields revealed that the continuous EL is seen after bipolar injection from cathode and anode, thereby pointing towards a mechanism of excitation due to charge recombination [28,29].…”
Section: Electroluminescence Detectionmentioning
confidence: 97%
“…In some way, it could explain why results are not fairly reproducible regarding the quantitative aspects of the signal being measured. Under AC stress, part of the signal being detected has been explained by surface plasmon resulting from collective excitations of carriers on the metallic electrodes [4]. Such kind of emission is localized on 'hot spots' in the sample plane.…”
Section: Discussionmentioning
confidence: 99%